Multimodal shunt damping of mechanical structures using multiple digital vibration absorbers. (1st December 2022) - Dietrich, Jennifer; Raze, Ghislain; Kerschen, Gaëtan
Abstract: A novel piezoelectric shunt damping methodology for structures featuring different mode families with high modal density is introduced in this work. To this end, multiple digital vibration absorbers comprising each a voltage sensor, a digital processing unit and a current injector are connected to multiple piezoelectric transducers bonded to these structures. The digital absorbers mimic a multi-stage current blocking shunt circuit whose parameters are determined in a sequential manner to account for the interaction between the different branches. Two tuning strategies which target either an actual resonance frequency of a mode family or a so-called mean frequency are developed and compared, and their robustness to mistuning is addressed. The use of these tuning strategies in combination with the multi-stage shunt design allows to target multiple mode families at the same time. Finally, the theoretical developments are demonstrated experimentally on a 3D-printed rail with 5 blades.